Autochthonous Canine Visceral Leishmaniasis in Urban Area of Porto Alegre, RS, Brazil - Bianchi, Matheus Viezzer; Fredo, Gabriela; Tagliari, Nelson Junior; Filho, Ronaldo Viana Leite; de Lorenzo, Cintia; Lupion, Camila Gottlieb; Driemeier, David; Sonne, Luciana (Acta Scientiae Veterinariae, 2016)
Background: Leishmaniasis is a chronic infectious disease caused by intracellular protozoan Leishmania that affects canine and human. The visceral leishmaniasis (VL) is caused by the Leishmania donovani complex, in which canines are the main reservoir for human VL. In Southern Brazil, case reports of this disease have increased, especially when canines are infected in endemic areas in the country. Canines usually present a systemic disease, characterized by cutaneous lesions, weight loss, generalized lymphadenopathy, hepatomegaly and splenomegaly. This report aims to describe the clinicalpathological features of a case of autochthonous VL in a canine of an urban area of Porto Alegre. Case: A male, mixed breed, dog , 7 year-old, resident at the East Side of Porto Alegre, living together with two other canines, presented at clinical examination progressive weight loss, associated with hyporexia and hyperthermia, evolving to lateral recumbency, paralisys, and death. At necropsy, the dog was cachectic with diffusely pale mucosae. Gross findings included liver enlarged, with multifocal firm brownish areas, spleen enlarged, showing multifocal firm round dark-red areas, and kidneys diffusely pale with evidentiated tranversal striations on cortical zone. At microscopic examination, there was on the spleen diffuse inflammatory infiltrate of macrophages with large cytoplasm containing multiple amastigotes. The liver, exhibited atrophy of hepatocytes and moderate multifocal inflammatory infiltrate in sinusoids of macrophages containing multiple amastigotes. These features were also observed moderately on lymph nodes and lamina propria of large intestine. Immunohistochemistry examination showed marked positive staining for Leishmania spp. in amastigotes located whitin the cytoplasm of macrophages of spleen, liver, lymph nodes and large intestine. Discussion: Canine leishmaniasis is a disease that affects both internal organs and skin. However, the condition is called VL mostly because it is associated with the same species that cause the visceral form in humans. In this case the canine presented liver, spleen and lymph node lesions; however no skin lesion was observed during the clinical examination. A serological evaluation of canids in East Side of Porto Alegre performed in 2005 showed that 3.5% of these dogs were positive for Leishmania; yet neither of these animals presented clinical signs. This demonstrates that the agent was already present, however only 3-10% of the canines infected develop clinical disease. In non-endemic areas VL is related to the migration of canids from endemic areas, where VL is common. However the canine here described was born, raised, and was living in Porto Alegre. Lutzomyia longipalpis is the main vector of VL and despite its wide distribution it was identified only in 2009 in Rio Grande do Sul State. Autochthonous cases of VL were reported in canines and humans in this state, confirming the hypothesis that the vector was widely distributed and it is now present in Porto Alegre, keeping the epidemiological cycle of that disease active. Canine VL occurs prior in humans, since canines are the main domestic reservoirs and are critical for the maintenance of this disease cycle. This is the first autochthonous VL in a canine of an urban area of Porto Alegre; therefore authorities should be alert, and new control measures must be taken to avoid the canine leishmaniasis outbreak due to its potential for zoonotic transmission. Keywords: leishmaniasis, canine, protozoan, immunohistochemistry.